Die Rhein-Rhône-Verbindungen - Stang, Friedrich (ERDKUNDE, 1967)
The decision to build new canals over the water partings between the upper Rhine and the Saone and between the Moselle and the Saone is an important step towards modernizing the French waterway system and towards its integration into the navigation systems of neighbouring states. It is hoped that the planned Rhine-Rhone links will encourage the extension of Marseilles' hinterland and provide incentives for the location of industry in the areas served by the waterway. The attainment of this goal, however, requires the fulfilment of a number of further preconditions and acceptance of the fact that the costs of the waterway will not be fully covered.